Comprehensive lipidomics analysis reveals the changes in lipid profile of camellia oil affected by insect damage - Li, Qingyang; Zhang, Wei; Shen, Danyu; Li, Zhihong; Shu, Jinping; Liu, Yihua (Frontiers in Nutrition, 2022)
Information on changes in lipid compositon of seed oils under biotic stresses is scare. The camellia weevil, Curculio chinensis (Coleoptera: Curculionidae) as a notorious seed predator of Camellia species, has caused huge economic losses in China. Lipidomics is used in this study to reveal the lipid composition of camellia oil and its changes after insect damage. 278 lipids including glycerolipids (GL) (221), glycerophospholipids (GP) (34) , fatty acyls (FA) (13), sphingolipids (SP) (8), prenol lipids (PR) (1) and sterol lipids (ST) (1) were determined in camellia oils. Insect damage had a significant impact on lipids, particularly FA and GL. Ten significantly different lipids (FFA(18:2), FFA(24:6), TG(14:1/18:2/18:2), TG(16:0/23:0/18:2), TG(20:1/24:1/18:2), TG(18:2/24:0/18:2), TG(16:3/18:2/22:5), PI(16:1/18:1), PE(16:0/18:1), PE(18:1/18:2)) were identified as potential biomarkers for distinguishing oil extracted from non-infested oilseeds and oil from infested oilseeds. We also detected four most important metabolic pathways by bioinformatics analysis to explore the mechanisms underlying changes. Our findings may be useful for future camellia oil production and may provide new insight into improving of nutritional quality of camellia oil.